System Expert Diagnosis Iphone Cellphone Damage Web-Based - Hadi Nugroho, Donny; Fairuzabadi, M.; Nonsi Tentua, Meilany; Nor Azhari Azman, Mohamed (Lembaga Penelitian dan Pengabdian Mayarakat (LPPM) Universitas PGRI Yogyakarta, 2022)
Mobile phones (HP) or smartphones are the most popular communication tools used by the public. Based on interviews with several mobile phone users and technicians, the iPhone is currently one of the best-selling and most prestigious brands. But in reality, the iPhone user community, in general, does not understand the damage that often occurs to HP. This leads users to bring the damaged HP to the service point without knowing in advance what kind of damage occurred to the HP. The study aims to build an app to diagnose damage to web-based iPhone phones. In collecting the data needed for the study, the authors used methods of literature study, interviews, and observation. This web-based iPhone mobile damage diagnostic system application is made using the PHP programming language. The game development stage includes analysis, system design, implementation, and testing. The expert system application to diagnose damage to the web-based iPhone phone that is made can be used to find out the damage to the iPhone phone, before being taken to the service so that users know what damage is repaired. The results of system testing showed that this application is feasible and can be used as a web-based iPhone mobile damage diagnostic system application.